2009
DOI: 10.1002/chem.200900958
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting DNA–DNA Interstrand Cross‐Links in the Antiparallel 3′–3′ Sense: A Comparison with the 5′–5′ Directional Isomer

Abstract: Reported herein is a study of the unusual 3′-3′ 1,4-GG interstrand cross-link (IXL) formation in duplex DNA by a series of polynuclear platinum anticancer complexes. To examine the effect of possible preassociation through charge and hydrogen-bonding effects the closely related compounds [{trans-PtCl(NH 3 ) 2 } 2 (μ-trans-Pt(NH 3 ) 2 -{NH 2 (CH 2 ) 6 NH 2 } 2 )] 4+ (BBR3464, 1), [{trans-PtCl (NH 3 ) 2 } 2 (μ-NH 2 (CH 2 ) 6 -NH 2 )] 2+ (BBR3005, 2), [{trans-PtCl-(NH 3 ) 2 } 2 (μ-H 2 N (CH 2 ) 3 NH 2 (CH 2 ) 4 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 40 publications
4
48
0
2
Order By: Relevance
“…7, 8, 14 To allow for direct comparison with previous studies (and particularly the reaction of 1,1/ t,t with duplex I ) 13 similar conditions were chosen (pH 5.4, 298 K). The 1 H NMR spectra recorded immediately after addition of 1 to duplex I showed splitting in the G7, G18 and G25 imino proton resonances (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 8, 14 To allow for direct comparison with previous studies (and particularly the reaction of 1,1/ t,t with duplex I ) 13 similar conditions were chosen (pH 5.4, 298 K). The 1 H NMR spectra recorded immediately after addition of 1 to duplex I showed splitting in the G7, G18 and G25 imino proton resonances (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 In contrast, studies with 5′ – d{TATACTA G TATA} 2 ( III ) (now 3′ –3′ ) showed that the pre-association and aquation steps were similar but the reaction did not yield a single distinct 1,4-GG IXL, and numerous cross-linked adducts formed. 8 Molecular dynamics simulations showed a highly distorted structure with fraying of the end base pairs and considerable widening of the minor groove. 8 The results suggest that the multiple DNA cross-links available to BB3464 may all contribute substantially to its cytotoxicity, so that the overall drug cytotoxicity could be the sum of the contributions of different interstrand and intrastrand adducts.…”
Section: Introductionmentioning
confidence: 99%
“…For multinuclear platinum complexes it has been shown that hydrogen bonding and electrostatic binding between the bridging ligand and the DNA helix is important in stabilising and directing the type of DNA adducts formed. 19,[26][27][28] The ligands synthesised in this work are therefore capable of acting as both hydrogen bond acceptors/donors and when pre-associated in the DNA minor groove, can potentially form hydrogen bonds to the bases as well as ion-dipole interactions with the anionic DNA backbone.…”
Section: Ligand Synthesismentioning
confidence: 99%
“…Molecular 3d-metal clusters continue to attract attention [1] due to potential applications as catalysts for organic synthesis [2][3][4][5], models of metal-containing sites in biology [6][7][8], and single molecular magnets [9][10][11][12] or single chain magnets [13,14]. A synthetic challenge involves discovering simple and suitable ligands, which possess arrays of coordination pockets organized to create high-nuclearity molecules.…”
Section: Introductionmentioning
confidence: 99%